Oltre lo sprawl? Ambizioni, successi e problemi irrisolti Uno studio della gestione del suolo a Portland, Denver e Minneapolis - Manella, Gabriele (Sociologia del territorio, 2021)
Urban settlements are critical today, not only in demographic, economic and cultural terms, but also for their environmental impact. A sustainable land management is therefore a fundamental requirement. Urban sprawl has long been described as settlement model that is unsustainable from all the points of view, but its growth has been virtually unchallenged for decades. Many regions have recently become aware of the problem however, and they are trying to tackle this challenge. This book tries to focus on this challenge and it moves from the following research questions: which outcomes have been obtained against sprawl? Which difficulties emerged? Who and why is against these policies? Which are the "unwanted effects" of these policies? The book is focused on the US trends, where the problem emerged first. Portland, Denver and Minneapolis are considered: three metropolitan regions in different parts of the country but with similar dimensions, characteristics and policies. The conditions that made some outcomes possible are highlighted (the ability to network institutions at multiple levels and to foster the participation of local actors in the land management process), as well as some critical issues and unsolved problems (the exponential growth of real estate costs, the opposition of a part of the local community, the persistence of segregation and inequality forms).